Properties of Biomimetic Artificial Spider Silk Fibers Tuned by PostSpin Bath Incubation - Greco, Gabriele (Molecules, 2020)
Efficient production of artificial spider silk fibers with properties that match its natural counterpart has still not been achieved. Recently, a biomimetic process for spinning recombinant spider silk proteins (spidroins) was presented, in which important molecular mechanisms involved in native spider silk spinning were recapitulated. However, drawbacks of these fibers included inferior mechanical properties and problems with low resistance to aqueous environments. In this work, we show that ≥5 h incubation of the fibers, in a collection bath of 500 mM NaAc and 200 mM NaCl, at pH 5 results in fibers that do not dissolve in water or phosphate buffered saline, which implies that the fibers can be used for applications that involve wet/humid conditions. Furthermore, incubation in the collection bath improved the strain at break and was associated with increased β-sheet content, but did not affect the fiber morphology. In summary, we present a simple way to improve artificial spider silk fiber strain at break and resistance to aqueous solvents.